La incorporación de la cláusula social y el funcionamiento del mercado. Dudas sobre su efectividad - Alvares Garcia Júnior, Armando (2016)
This article analyzes the efficiency of the so-called «social clause» (clause of protection of human and labor rights) incorporated into bilateral trade agreements concluded between the European Union and developing countries, both from the perspective of the market performance (first part of the article) and its acceptability in the Latin American and European context (second part).